2019
DOI: 10.1007/s10551-019-04298-2
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Auditors’ Sustained Ethical Behavior: Increased Trust and Reduced Costs

Abstract: Studies demonstrating the benefits of ethical behavior at an individual level are scarce. The business ethics literature centers its analysis on unethical behaviors and their consequences, rather than ethical behaviors and their benefits. There is now considerable debate on the role of auditors in society and the function of accounting firms in the free market capitalist system. Specifically, the eminently ethical nature of the auditor's work has been highlighted. Therefore, the aim of our paper is to show the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 103 publications
1
8
0
2
Order By: Relevance
“…It has been reported that those who are not trusting a seller are unlikely to be loyal (Palacios-Florencio et al , 2018). It is also documented that the seller’s ethical behaviour can generate trust (Morales-Sánchez et al , 2019). Therefore, sellers that practice ethical sales obtain a higher degree of commitment from their customers and, simultaneously, increase customers’ trust in the company.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been reported that those who are not trusting a seller are unlikely to be loyal (Palacios-Florencio et al , 2018). It is also documented that the seller’s ethical behaviour can generate trust (Morales-Sánchez et al , 2019). Therefore, sellers that practice ethical sales obtain a higher degree of commitment from their customers and, simultaneously, increase customers’ trust in the company.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Then there's the research on ethical behavior at the individual level (Morales-Sánchez et al, 2020). Nonetheless, ethical behavior is at the basis of the accounting profession, particularly among auditors, who are expected to adhere to a strict code of ethics (Mubako et al, 2020).…”
Section: H 1 : Personal Values Affect Ethical Behaviormentioning
confidence: 99%
“…Research conducted by Morales et al (2020) examines the impact of professional auditors' ethical behavior on auditor trust. There are so many interpretations of trust or trust from various fields of science.…”
Section: H 1 : Personal Values Affect Ethical Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Keputusan etis diartikan sebagai keputusan dari perspektif hukum maupun etis dapat diterima dengan baik oleh masyarakat umum (Hazgui dan Brivot, 2020). Fokus perilaku etis pemeriksa BPK adalah mengkritisi apa yang baik atau buruk dari perspektif moral, dan outcome dari perilaku etis tersebut tidak diukur dalam keuntungan material, tetapi terletak pada nilai intrinsiknya, dimana ketika seorang pemeriksa BPK berperilaku etis maka akan menghasilkan kepercayaan di lingkungan mereka dan masyarakat (Morales-Sánchez, Orta-Pérez dan Rodríguez-Serrano, 2019). Tidak hanya terbatas pada pemeriksa BPK, berperilaku etis merupakan sebuah kewajiban bagi semua kompartemen auditor karena mempengaruhi kredibilitas profesinya.…”
Section: Dilema Etis Pemeriksa Bpkunclassified